Who chooses whom for professional interaction? A sociometric inquiry into teacher leadership - ÇETİN, MÜNEVVER (My University, 2023)
Given the dyadic and multi-layered nature of professional relations, informal teacher learning mostly goes through complex, non-linear, and context-dependent professional interactions. Advice-seeking relationships (ASRs) are the most common form of informal interactions between teachers. However, due mostly to analytical constraints, little is known about the factors influencing ASRs in school settings. The paper aims to provide an empirical base for understanding the informal leadership exercised through between-teacher ASRs around technological and pedagogical expertise. To that end, inferential social network analysis (SNA) techniques are employed. Results showed teacher perception of positive school culture promotes pedagogical ASRs. Administrative leadership is significant in one-way advice flows from administrators to subordinates. Interpersonal similarities by gender and teaching experience are influential in peer selection for ASRs. Hybrid-expertise teachers, being equally headed for technological and pedagogical advice, occupy more central position in advice-networks. Regardless of school culture, technology-savvy teachers are more preferred for ASRs. The more teachers provide colleagues with technological advice, the more they assume a leading position for pedagogical advice, but not vice versa. Overall, the present SNA study sheds light on relational complexities of teacher leadership for professional learning that otherwise might not be salient when investigated using linear models on individual metrics.
Keywords: Sosyal ve Beşeri Bilimler; Sosyoloji; Eğitim; Social Sciences and Humanities; Sociology; Education; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; advice networks; exponential random graph models; organisational learning; professional interactions; social network analysis; teacher leadership